Enteric β-Defensin: Molecular Cloning and Characterization of a Gene with Inducible Intestinal Epithelial Cell Expression Associated with Cryptosporidium parvum Infection - Tarver, Alan P. (American Society for Microbiology, 1998)
A growing body of evidence suggests that endogenous antibiotics contribute to the innate defense of mammalian mucosal surfaces. In the cow, β-defensins constitute a large family of antibiotic peptides whose members have been previously isolated from the respiratory and oral mucosa, as well as circulating phagocytic cells. A novel bovine genomic clone with sequence related to those of these α-defensins was isolated and characterized. The corresponding cDNA was isolated from a small intestinal library; its open reading frame predicts a deduced sequence of a novel β-defensin, which we designate enteric β-defensin (EBD). Northern blot analysis of a variety of bovine tissues revealed that EBD mRNA is highly expressed in the distal small intestine and colon, anatomic locations distinct from those for previously characterized β-defensins. EBD mRNA was further localized by in situ hybridization to epithelial cells of the colon and small intestinal crypts. Infection of two calves with the intestinal parasite Cryptosporidium parvum induced 5- and 10-fold increases above control levels of EBD mRNA in intestinal tissues. An anchored-PCR strategy was used to identify other β-defensin mRNAs expressed in the intestine. In addition to that of EBD, several low-abundance cDNAs which corresponded to other β-defensin mRNAs were cloned. Most of these clones encoded previously characterized β-defensins or closely related isoforms, but two encoded a previously uncharacterized prepro-β-defensin. Northern blot evidence supported that all of these other β-defensin genes are expressed at levels lower than that of the EBD gene in enteric tissue. Furthermore, some of these β-defensin mRNAs were abundant in bone marrow, suggesting that in enteric tissue their expression may be in cells of hematopoietic origin. Extracts of small intestinal mucosa obtained from healthy cows have numerous active chromatographic fractions as determined by an antibacterial assay, and one peptide was partially purified. The peptide corresponded to one of the low-abundance cDNAs. This study provides evidence of β-defensin expression in enteric tissue and that the mRNA encoding a major β-defensin of enteric tissue, EBD, is inducibly expressed in enteric epithelial cells. These findings support the proposal that β-defensins may contribute to host defense of enteric mucosa.